Diques mesozoicos básicos e intermediários como condicionantes do relevo na porção noroeste da Ilha de São Sebastião - SP - Valle, Victor Arroyo da Silva do [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The study of aspects related to relief evolution is an important tool for achieving an optimal management of the environment in which we live and extract essential resources to the modern life. The analysis of factors responsible for the origin of determined landforms is an example of those studies. In the case of the study area, the northwest portion São Sebastião Island (SP), different landforms are related to distinct geological units. The main units described in the area are: a Precambrian granite-gneissic basement, Mesozoic basic and intermediate dykes, and Mesozoic alkaline stocks and dykes. The landforms associated with the basic and intermediate dykes show an interesting pattern. There are cases in which they are characterized by elongated ridges, which represent landforms that are more resistant to surface processes (weathering and erosion). In other cases, they define the course of streams, therefore, representing landforms that are less resistant to surface processes. In that context, the main objective of this study is to identify which factors determine the resistance of the dykes to surface processes, and, therefore, are responsible for the landforms associated with them. In order to achieve that objective, a characterization of the dykes was made focusing aspects such as mineralogical composition, structural pattern, rock age, and the characteristics of the relief units in which the dykes are present. A comparative chart containing aspects related to both dykes and basement was prepared in order to establish which of those aspects are in fact responsible for the different landforms associated with the dykes. The obtained results indicate that the mineralogical composition, the fracture pattern and the thickness of the dykes are the main factors that determine the resistance of those rocks to ... (Complete abstract electronic access below)

O estudo de aspectos relacionados à evolução do relevo é uma ferramenta importante para a melhor gestão do ambiente no qual vivemos e extraímos recursos essenciais à vida moderna. Como exemplo, cita-se a análise dos fatores responsáveis pela gênese de determinadas formas de relevo. No caso da área de estudo, a porção noroeste da Ilha de São Sebastião (SP), são descritas diversas formas de relevo associadas principalmente a distintas unidades geológicas. Destacam-se um embasamento pré-cambriano granito-gnáissico, diques mesozoicos de rochas básicas e intermediárias, e stocks e diques também mesozoicos de rochas alcalinas. Dentre tais litotipos, os diques básicos e intermediários exibem interessante resposta do relevo. Por vezes, eles são associados a cristas alongadas, ou seja, feições positivas mais resistentes aos processos superficiais (intemperismo e erosão). Já em outros casos, os diques definem o curso de drenagens, representando assim feições negativas menos resistentes aos processos superficiais. Nesse contexto, o principal objetivo do presente estudo é identificar quais fatores são determinantes na resistência dos diques aos processos superficiais e, portanto, responsáveis pelas diferentes formas de relevo associadas a eles. Para tanto, optou-se por realizar uma caracterização dos mesmos quanto a sua resposta aos processos modeladores do relevo, evolvendo não somente sua composição litológica, mas também sua estruturação, idade e as características das unidades de relevo nas quais os diques estão inseridos. Desse modo, foi elaborado um quadro comparativo contendo características tanto dos diques quanto do embasamento no qual eles estão intrudidos para que fosse possível estabelecer quais fatores são de fato responsáveis pelas diferentes ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Geomorfologia; Diques (Geologia); Relevo; São Sebastião (SP)